Our experience of treating children with primary monosymptomatic enuresis nocturna in a pediatric bedwetting clinic - Karakaya, Ali Erdal (Journal of Surgery and Medicine, 2021)
Background/Aim: Enuresis nocturna is an important problem that negatively affects the self-confidence and quality of life of millions of children. Controversial points still exist regarding the treatment algorithm of enuresis. This study aimed to discuss the approach to this condition which deeply affects the child and their family and contribute to the literature by analyzing the success in the treatment steps. Methods: This study was conducted by reviewing the files of the patients who presented to the pediatric bedwetting outpatient clinic between May 2017 and March 2019 with the complaint of nocturia. The diagnoses and treatment outcomes were recorded from the patient files. The first step was motivation therapy, the second step was alarm treatment, and the third step was drug therapy, which were combined if necessary. Results: Among 95 primary monosymptomatic enuresis nocturna patients with a mean age of 8.5 years, all patients received supportive treatment to increase motivation as the first step. The second step consisted of alarm treatment administered to 32 patients and as the third step, medical drug treatment was prescribed to eight. Enuresis decreased in 58% of the patients receiving motivation therapy, 63% of the patients receiving alarm therapy and >90% of the patients receiving drug therapy; however, it relapsed when the medication was discontinued. Conclusion: According to the experience acquired in this study, a specific enuresis polyclinic is important in terms of ease of presentation for patients, and motivation treatment should be the first line of treatment. Other treatment steps can be added as necessary. All three steps in primary monosymptomatic enuresis nocturna can be combined or administered alone.